Scientific Opinion on the safety evaluation of the following processes based on EREMA Advanced technology used to recycle post‐consumer PET into food contact materials: 'Greentech', 'Alimpet' and 'Polyrecycling'. (17th February 2015) - ,; ,
Abstract: This scientific opinion of the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) deals with the safety assessment of the recycling processes Greentech, Alimpet and Polyrecycling (EU register numbers RECYC112, RECYC114 and RECYC119, respectively), all of which are based on the same EREMA Advanced technology. The input to these processes is washed and dried polyethylene terephthalate (PET) flakes originating from collected post‐consumer PET containers, mainly bottles, containing no more than 5 % PET from non‐food consumer applications. In this technology, washed and dried PET flakes are heated successively in two continuous reactors before being extruded into pellets. Having examined the results of the challenge test provided, the Panel concluded that the continuous reactor step (step 3) is the critical step that determines the decontamination efficiency of these processes. The operating parameters which control the performance of this step are well defined and are temperature, pressure and residence time. It was demonstrated that the recycling processes under evaluation are able to ensure that the level of migration of potential unknown contaminants into food is below a conservatively modelled migration of 0.1 μg/kg food, derived from the exposure scenario for infants, and 0.15 μg/kg food, derived from the exposure scenario for toddlers. The Panel concluded that recycled PET obtained from these processes is not of safety concern when used to manufacture articles intended for food contact materials applications if it is produced in compliance with the conditions specified in the conclusion of this opinion.